Association of Physical activity levels and BMI Among Doctor of Physical Therapy Students of a Private College from Karachi - Khalid Aziz; Ayesha Afridi; Abida Arif; Ghousia Shahid; Muhammad Faisal Fahim; Rabia Khan (Journal of Bahria University Medical and Dental College)
ABSTRACT: Objective: To evaluate the physical activity levels among DPT students of Bahria University College of Physical therapy (BUCPT) by International Physical Activity Questionnaire (IPAQ) and to study the relationship between Body Mass Index (BMI) and Physical activity levels of DPT students of (BUCPT). Study design and Setting: This cross sectional study was conducted in BUCPT Bahria from March- April 2019 (1 month data collection). Methodology: Written consent form was obtained from each participant before taking part into study. Individual with cardio-respiratory diseases and fractures in last 12 months or any limb disability were excluded from the study. The study tool was IPAQ. Results:A total of 125 students were enrolled in this study. There were 121 (96.8%) female and 4 (3.2%) male observed. Mean age of students were 19.89±1.14 (18-22) years. In low physical activity level, 2 (28.6%) students were underweight, 8 (17.0%) were normal BMI, 3 (9.7%) were overweight and 6 (15.0%) were obese. In moderate physical activity level, 3 (42.9%) underweight, 22 (46.8%) normal, 19 (61.3%) overweight and 19 (47.5%) fall in obese criteria. High physical activity levels were found to be 2 (28.6%) in underweight group, 17 (36.2%) in normal group, 9 (29.0%) in overweight and 15 (37.5%) were obese. Conclusion: BUCPT students were moderately physically active and minority of them were low physically active and majority of them were lying the category of normal BMI. There was statistically insignificant relationship found between BMI and physical activities levels. Some students were obese and still have high physical activity level while some are normal in BMI and having low physical activity level